Human Immunodeficiency Virus-Associated Chronic Lung Disease in Children and Adolescents in Zimbabwe: Chest Radiographic and High-Resolution Computed Tomographic Findings. (4th September 2017) - Desai, Sujal R; Nair, Arjun; Rylance, Jamie; Mujuru, Hilda; Nathoo, Kusum; McHugh, Grace; Majonga, Edith; Metcalfe, John; Kranzer, Katharina; Ferrand, Rashida A
Abstract : There is a substantial burden of chronic lung disease among treated children with human immunodeficiency virus infection in this study from Zimbabwe. The radiological findings, coupled with functional test results, indicate that the key pathological lesion is constrictive obliterative bronchiolitis. Abstract: Background: Chronic respiratory symptoms are common among children living with human immunodeficiency virus (HIV). We investigated the radiological features of chronic lung disease in children aged 6–16 years receiving antiretroviral therapy for ≥6 months in Harare, Zimbabwe. Methods: Consecutive participants from a HIV clinic underwent clinical assessment and chest radiography. Participants with an abnormal chest radiograph (assessed by a clinician) and/or those meeting a clinical case definition for chronic lung disease underwent high-resolution computed tomography (HRCT). Radiological studies were scored independently and blindly by 2 thoracic radiologists. Relationships between radiological abnormalities and lung function were examined. Results: Among 193 participants (46% female; median age, 11.2 years; interquartile range, 9.0–12.8 years), the median CD4 cell count was 720/µL (473–947/µL), and 79% had a human immunodeficiency virus (HIV) load of <400 copies/mL. The most common chest radiographic finding was ring/tramline opacities (55 of 193 participants; 29%). HRCT scans were evaluated in 84 participants (69%); decreased attenuation (present in 43%) was the dominant abnormality seen. The extent of decreased attenuation was strongly correlated with both the severity and extent of bronchiectasis ( r s = 0.68 and P < .001 for both). The extent of decreased attenuation was also negatively correlated with forced expiratory volume in first second of expiration ( r s = –0.52), forced vital capacity ( r s = –0.42), and forced expiratory flow, midexpiratory phase ( r s = –0.42) ( P < .001 for all). Conclusions: The HRCT findings strongly suggest that obliterative bronchiolitis may be the major cause of chronic lung disease in our cohort. Further studies to understand the pathogenesis and natural history are urgently needed.